ผลของฤดูการเก็บเกี่ยวต่อลักษณะรูปแบบทางเคมีของสารสำคัญในใบพลู - สิงห์ทองรัตน์ นิรมล; สิงขรรัตน์ จิรดา; วัฒนสินธุ์ สุมณฑา (Thai Journal of Science and Technology, 2013)
<!–[if gte mso 9]> Normal 0 false false false EN-US X-NONE TH <![endif]–> บทคัดย่อ ผลกระทบของช่วงเวลาการเก็บเกี่ยวต่อคุณภาพของสารสกัดใบพลูจากเทคนิคการสกัดด้วยของไหลยวดยิ่งรายงานโดยอาศัยเทคนิคโครมาโตกราฟีของเหลวสมรรถนะสูงในการวิเคราะห์ปริมาณสารสำคัญหลัก ได้แก่ อัลลิวไพรอแคทีชอล และยูกีนอล ผลที่ได้แสดงให้เห็นว่าปริมาณของสารสกัดจากใบพลูที่เก็บเกี่ยวในตอนปลายฤดูฝนมีแนวโน้มการพบสารอัลลิวไพรอแคทีชอลสูงที่สุด และยูกีนอลต่ำ ซึ่งตรงกันข้ามกับสารสกัดใบพลูที่เก็บเกี่ยวในช่วงหน้าแล้ง สารสำคัญในใบพลูแสดงการเปลี่ยนแปลงตามฤดูการเก็บเกี่ยวที่ต่างกัน โดยมีปัจจัยชักนำจากปริมาณน้ำในแต่ละฤดูกาล ซึ่งส่งผลกระทบต่อการเปลี่ยนรูปของสารในกลุ่มโพรพินิลฟีนอล คำสำคัญ : ใบพลู; อัลลิวไพรอแคทีชอล; ยูกีนอล; ฤดูการเก็บเกี่ยว Abstract The harvest effect of supercritical fluid extraction extracts on quality of betel-leaf extracts (Piper betle Linn.) has been reported. A high performance liquid chromatographic (HPLC) method was used for quantitative determination of allypyrocatechol (APC) and eugenol in extracts of Piper betle Linn. The extract from betle leaves harvested in late rainy season showed the highest amount of APC and the low amount of eugenol in contrast to those harvested in summer period. The results indicated that harvest date effected on composition of betel-leaf extracts. The water supply impact in each season could cause bioactive compound transformation in betel leaves, especially those in propenylphenol derivatives. Keywords: Piper betle Linn.; allylpyrocatechol; eugenol; harvesting season <!–[if gte mso 9]> <![endif]–><!–[if gte mso 10]> <mce:style><! /* Style Definitions */ table.MsoNormalTable mso-style-name:ตารางปกติ; mso-tstyle-rowband-size:0; mso-tstyle-colband-size:0; mso-style-noshow:yes; mso-style-priority:99; mso-style-parent:""; mso-padding-alt:0cm 5.4pt 0cm 5.4pt; mso-para-margin:0cm; mso-para-margin-bottom:.0001pt; mso-pagination:widow-orphan; font-size:10.0pt; font-family:"Times New Roman","serif"; mso-bidi-font-family:"Angsana New"; –> <!–[endif] –>